VD_FINDINFO Jug / 2012 / 263 vom 11. September 2012 - VD Tribunal cantonal (2012)
AFFILIATION À UNE BANDE, DOMMAGE MATÉRIEL, VOLDROIT PÉNAL, VOL D'USAGE, TENTATIVEDROIT PÉNAL, PAR MÉTIER | 106 CP, 139 ch. 1 CP, 139 ch. 2 CP, 139 ch. 3 CP, 144 al. 1 CP, 186 CP, 22 CP, 252 CP, 90 ch. 1 LCR, 94 ch. 1 al. 1 LCR, 95 ch. 1 al. 1 LCR, 96 ch. 2 LCR, 97 ch. 1 al. 1 LCR, 97 ch. 1 al. 7 LCR, 115 LEtr